KECERDASAN EMOSIONAL SISWA SMP AL-LATHIFI GONDANGLEGI - lailatul rofiah; Ahmad Danial Yogatsani; Wafiyatu Maslahah (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2026)
Education is not solely dependent on IQ, but also on emotional intelligence, which includes emotional regulation, empathy, motivation, and social skills. Observations at SMP Al-Lathifi Gondanglegi indicate that students with high emotional intelligence tend to be more active and cooperative, while teacher interventions have been proven to improve positive attitudes and learning outcomes among students with lower emotional intelligence. This study employed a qualitative case study approach at SMP Al-Lathifi Gondanglegi, involving a social studies teacher, a homeroom teacher, and six 8th-grade students as subjects. Data were collected through observation, interviews, and documentation, validated using triangulation, and analyzed with Miles & Huberman’s model through data reduction, presentation, and interactive conclusion drawing. The findings reveal that emotional intelligence plays a crucial role in social studies learning at SMP Al-Lathifi Gondanglegi. Students with high emotional intelligence can manage emotions, self-motivate, and maintain good relationships, leading to active and cooperative participation in class. Conversely, students with low emotional intelligence tend to struggle with controlling negative emotions, show less engagement in learning, and achieve lower academic results. Overall, the study indicates that while students’ emotional intelligence is developing positively, it remains unstable. Support from both schools and families is essential to enhance emotional intelligence for academic success and character development